Automating bioanalytical sample analysis through enhanced system integration. (July 2013) - Patel, Vimal; Leach, Daniel; Hornberger, Mark; Williams, Kathi; Shih, Judy; Ma, Mark; Laycock, John
Background: In the bioanalytical laboratory, challenges associated with manual, repetitive, labor-intensive processes can be addressed by powerful automated liquid handlers; however, their implementation has been difficult due to lack of efficient integration into laboratory workflows. Faster throughput is afforded to ligand binding assay (LBA) technologies via enhanced automation, but the upstream sample processing still remains a bottleneck. To be truly efficient, these technologies must be incorporated into a laboratory information management system (LIMS) to streamline data analysis and reporting.Results: Three off-the-shelf technologies that aid in improving bioanalytical laboratory efficiencies were utilized with minimal customization to streamline the sample analysis process. Information extracted via a sequence file from the LIMS run was utilized to perform the sample processing on the automated liquid handler. A file conversion tool converted the sequence files that allowed for sample processing and preparing the assay ready plate. The plate was then transferred to the LBA microfluidics platform to run the experiments. The integration was tested using a LBA PK assay that demonstrated good sample dilution and assay performance.Conclusion: We successfully integrated LIMS with an automated liquid handler and a microfluidics platform to automate the sample analysis process in the bioanalytical laboratory. The utilization of off-the-shelf technologies with minimal customization requires minimal resources from laboratory scientists. It may be possible to implement this approach for other analytical platforms.